Fibrin Stiffness Regulates Phenotypic Plasticity of Metastatic Breast Cancer Cells - Heilala, Maria; Lehtonen, Arttu; Arasalo, Ossi; Peura, Aino; Pokki, Juho; Ikkala, Olli; Nonappa; Klefström, Juha; Munne, Pauliina M. (Advanced healthcare materials, 2023)
The extracellular matrix (ECM)‐regulated phenotypic plasticity is crucial for metastatic progression of triple negative breast cancer (TNBC). While ECM faithful cell‐based models are available for in situ and invasive tumors, such as cell aggregate cultures in reconstituted basement membrane and in collagenous gels, there are no ECM faithful models for metastatic circulating tumor cells (CTCs). Such models are essential to represent the stage of metastasis where clinical relevance and therapeutic opportunities are significant. Here, CTC‐like DU4475 TNBC cells are cultured in mechanically tunable 3D fibrin hydrogels. This is motivated, as in circulation fibrin aids CTC survival by forming a protective coating reducing shear stress and immune cell‐mediated cytotoxicity and promotes several stages of late metastatic processes at the interface between circulation and tissue. This work shows that fibrin hydrogels support DU4475 cell growth, resulting in spheroid formation. Furthermore, increasing fibrin stiffness from 57 to 175 Pa leads to highly motile, actin and tubulin containing cellular protrusions, which are associated with specific cell morphology and gene expression patterns that markedly differ from basement membrane or suspension cultures. Thus, mechanically tunable fibrin gels reveal specific matrix‐based regulation of TNBC cell phenotype and offer scaffolds for CTC‐like cells with better mechano‐biological properties than liquid. 3D fibrin gels are used to model the phenotypic plasticity of circulating tumor cells (CTCs) ‐like breast cancer cells. Compared with standard 3D culture conditions, cells in fibrin gels show unique gene expression signatures. The cell phenotype is subject to regulation by matrix mechanical properties, with stiff fibrin inducing dynamic cell protrusions that resemble prometastatic structures.